Lipids help double‐stranded RNA in endosomal escape and improve RNA interference in the fall armyworm, Spodoptera frugiperda. Issue 4 (15th April 2020) - Gurusamy, Dhandapani; Mogilicherla, Kanakachari; Shukla, Jayendra Nath; Palli, Subba Reddy
Abstract: RNA interference (RNAi) is a valuable method for understanding the gene function and holds great potential for insect pest management. While RNAi is efficient and systemic in coleopteran insects, RNAi is inefficient in lepidopteran insects. In this study, we explored the possibility of improving RNAi in the fall armyworm (FAW), Spodoptera frugiperda cells by formulating dsRNA with Cellfectin II (CFII) transfection reagent. The CFII formulated dsRNA was protected from degradation by endonucleases present in Sf9 cells conditioned medium, hemolymph and midgut lumen contents collected from the FAW larvae. Lipid formulated dsRNA also showed reduced accumulation in the endosomes of Sf9 cells and FAW tissues. Exposing Sf9 cells and tissues to CFII formulated dsRNA caused a significant knockdown of endogenous genes. CFII formulated dsIAP fed to FAW larvae induced knockdown of iap gene, growth retardation and mortality. Processing of dsRNA into siRNA was detected in Sf9 cells and Spodoptera frugiperda larvae treated with CFII conjugated 32 P‐UTP labeled dsGFP. Overall, the present study concluded that delivering dsRNA formulated with CFII transfection reagent helps dsRNA escapes from the endosomal accumulation and improved RNAi efficiency in the FAW cells and tissues. Abstract : Delivering dsRNA formulated with lipids helps with its escape from the endosomes in the fall armyworm cells and tissues. dsRNA formulated with lipids improves RNAi efficiency in the fall armyworm cells and tissues. Phenotypes in pupae developed from larvae fed on CFII‐dsIAP or naked dsIAP CFII‐dsGFP or dsGFP. Research Highlights: Delivering dsRNA formulated with lipids helps with its escape from the endosomes in the fall armyworm cells and tissues. dsRNA formulated with lipids improves RNAi efficiency in the fall armyworm cells and tissues.